Estrategias de marketing para incrementar el posicionamiento de la Empresa Restaurante Cabaña Grill S.A.C. Trujillo 2015. - Mendoza Radas, Karyna Guisell (2016)
The principal purpose from this dissertation is going to improve marketing strategies to increase the positioning of Cabaña Grill S.A.C. restaurant company. The problem of this research is: In which way the marketing strategies can to increase the positioning of Cabaña Grill S.A.C. restaurant company in Trujillo? Based on the hypothesis that: The marketing strategies permit to increase in a good way the positioning of Cabaña Grill S.A.C. restaurant company in Trujillo. In order to achieve this I use the interactive communication to satisfice the need to be informed and requires of costumers. The variable of study are independent variable: marketing strategies and depend variable: positioning of Cabaña Grill S.A.C. restaurant company. I used the descriptive- transactional research design and the probabilistic method. The group of study was the costumers of Cabaña Grill restaurant. The study was realized with information provided by the company, survey to company´s clients and an interview with the manager of it. I elaborated the marketing strategies and surges to develop it in a correct way. I conclude that, the marketing strategies permit to increase in a good way the positioning of Cabaña Grill restaurant company, also it have to a competitive advantage which permit to Cabaña Grill restaurant to be different from their competence.